2011
DOI: 10.1071/cp11257
|View full text |Cite
|
Sign up to set email alerts
|

Seedling growth under osmotic stress and agronomic traits in Bulgarian semi-dwarf wheat: comparison of genotypes with Rht8 and/or Rht-B1 genes

Abstract: Early-season drought is an adverse environmental factor affecting seedling emergence and crop establishment in winter wheat grown in continental climates. The different semi-dwarfing (Rht, reduced height) genes exert various effects on seedling growth, plant height and productivity. The occurrence of the major Rht genes in 69 Bulgarian bread wheat cultivars was postulated by molecular markers. Cultivars carrying Rht-D1b+Rht8 (1) (43) were identified. The three latter groups were compared in respect to germinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…These results are in accordance with the earlier reports [38]. Coleoptile length and plant height are polygenic traits and many QTLs have been reported that influence traits [26], [28], [39][41].…”
Section: Discussionsupporting
confidence: 93%
“…These results are in accordance with the earlier reports [38]. Coleoptile length and plant height are polygenic traits and many QTLs have been reported that influence traits [26], [28], [39][41].…”
Section: Discussionsupporting
confidence: 93%
“…The modern semi‐dwarf varieties have been released at the Bulgarian main breeding centres—the Dobrudja Agricultural Institute, the Institute of Plant Genetic Resources, and the former Institute of Genetics, Sofia. The modern varieties carry the height reducing gene Rht8 (the 192 bp‐allele at locus Xgwm261 ) (Katya and Pobeda), Rht8 + Rht‐B1b/d (Rusalka, Enola and Lada), or the 174 bp‐allele at locus Xgwm261 (Lozen 6) (Ganeva et al., ; Landjeva, Karceva, Korzun, & Ganeva, ).…”
Section: Methodsmentioning
confidence: 99%
“…The distribution of Rht‐B1b is restricted mostly to cooler regions, although a recent trend of its spread to regions with frequent periods of early season drought, such as the countries in Southeastern Europe and Ukraine, was reported (Landjeva et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…It is currently widely adopted worldwide (Hedden 2003), whereas the latter allele is not commercially exploited although in certain environments, it might contribute to pre-harvest sprouting resistance (Flintham and Gale 1982). The distribution of Rht-B1b is restricted mostly to cooler regions, although a recent trend of its spread to regions with frequent periods of early season drought, such as the countries in Southeastern Europe and Ukraine, was reported (Landjeva et al 2011).…”
Section: Introductionmentioning
confidence: 99%